The antihyperlipidemic activities of enzymatic and acidic intracellular polysaccharides by Termitomyces albuminosus. (20th October 2016) - Zhao, Huajie; Li, Shangshang; Zhang, Jianjun; Che, Gen; Zhou, Meng; Liu, Min; Zhang, Chen; Xu, Nuo; Lin, Lin; Liu, Yu; Jia, Le
Highlights: Two modified polysaccharides (EIPS and AIPS) were obtained from IPS of T. albuminosus . Rhamnose was the vital monosaccharide in maintaining the physiological status. The antihyperlipidemic and hepatoprotective activities were investigated. Findings indicated that IPS, EIPS and AIPS had potential physiological effects. Abstract: Two polysaccharides, EIPS and AIPS were obtained by the hydrolysis of IPS from Termitomyces albuminosus, and their pharmacological effects on blood lipid profiles metabolism and oxidative stress were investigated. The results demonstrated that EIPS was superior to IPS and AIPS on reducing hepatic lipid levels and preventing oxidative stress by improving serum enzyme activities (ALT, AST, and ALP), serum lipid levels (TC, TG, HDL-C, LDL-C and VLDL-C), hepatic lipid levels (TC and TG), and antioxidant status (SOD, GSH-Px, CAT, T-AOC, MDA, and LPO). These conclusions indicated that EIPS, AIPS and IPS might be suitable for functional foods and natural drugs on preventing the high-fat emulsion-induced hyperlipidemia. In addition, the monosaccharide compositions of IPS and its hydrolyzate were also processed.